Patient-centered outcomes in treatment options for proliferative diabetic retinopathy - YannuzzNicolas A.; SmiddyWilliam E. (眼科学报; 卷 31, 编号 4 (December 2016): 《眼科学报》, 2016)
The Diabetic Retinopathy Clinical Research (DRCR) Network Protocol S demonstrated, in a prospective, randomized, multicenter trial, the non-inferiority of intravitreal ranibizumab (IVR) compared to panretinal photocoagulation (PRP) in the treatment of proliferative diabetic retinopathy (PDR) (1).